WEAR AND BIOCOMPATIBILITY PROPERTIES OF POLYPROPYLENE/PERIWINKLE SHELL PARTICULATES COMPOSITES FOR DENTAL IMPLANT APPLICATION - Dodo, R. M.; Musa, Z.; Abdulwahab, M.; Bello, K. A.; Abdullahi, U.; Hamisu, A. (FUDMA JOURNAL OF SCIENCES, 2022)
The present study explored wear and biocompatibility characteristics of polypropylene (PP)/ periwinkle shell particulates (PWS) composites for dental implant application. Wet-sliding the stainless steel ball against specimen disc revealed the abrasive wear behaviour of the composites under load and linear speed of 5 N and 10 cm/s respectively. In the wear tests, the specimens were wetted with simulated human saliva with and without sodium fluoride (NaF) additive. On the other hand, a mouse specimen was used to carry out a biocompatibility test. The composite demonstrated superb wear resistance at 40 and 50wt% reinforcement loading. Further, results showed that wear rate decreased considerably with increasing PWS content. Higher wear rate was noted on composites under condition of simulated human saliva with NaF addition. The biocompatibility test reveals that developed composite is harmless to the living tissues. Thus, PP/PWS composites could be recommended to be used as dental restorative material